(untitled) (Journal of Academic Research, 2025)
The research aims to identify the human impact that has caused, and continues to cause, the damage and loose of the archaeological monuments of the city of Leptis Magna. It is certain that this city, like other archaeological cities around the world, has suffered from negative human factors, such as: wars, encroachments, and thefts. In addition, to incorrect restoration work on its archaeological sites. The scientific orientation of this research focuses on identifying the most important human factors that have contributed, and continue to contribute, to the deterioration of the archaeological monuments of the city of Leptis Magna. It also aims to identify the most important human factors that have contributed to the losse of many of the city’s antiquities through its historical stages, specifically the types and numbers of lost antiquities. The historical and descriptive approaches have used to achieve the research objectives. The results, through tracing historical narratives and field visits to the city revealed the human factors that contributed, and continue to contribute to the damage to the archaeological monuments of the city of Leptis Magna. They also revealed the reasons for the loss of many of the city’s architectural elements. Key words Human impact, damage, losse, archaeological monuments, Leptis Magna.